PEMBINAAN PENGAJAR TK DALAM MEMAHAMI STATUS GIZI ANAK BALITA - T. Soegeng Partono; Fitriani Ulfatus S.; Atip Nurwahyuni (Universitas PGRI Semarang, 2012)
AbstractNutritional status is a person's nutritional state, in this case can be detected by means of anthropometry is to measure the size of the body, such as body weight (BW), height (TB), the circle of the upper arm (LLA). This activity is usually done by all people but must be trained first. At this time of devotion, Tim IKIP PGRI want to follow up the IBM program, which is a kindergarten teacher guidance in understanding the nutritional status of children under five by providing training in nutritional measurement, manufacturing gauges nutrition, simulation, and frequently asked questions. Targets in service activities include kindergarten teachers all Sukorejo Village, District Gunungpati, the city, include: Earth TK 44, TK An-Nur, and Kindergarten ABA 38 with the problems now being faced by them are: 1) lack of knowledge in identifying the nutritional status of children under five are visually, 2) lack of available gauges nutritional status, 3) lack of skill make gauge nutritional status, 4) non optimal use of nutrition among children under five gauges. Achievements of these faculty development activities in the village kindergarten Sukorejo able to understand the nutritional status of children under five with a good and able to measure nutritional status, and be able to apply the measure nutritional status (anthropometry) correctly. In addition, the service team is also providing a stimulus to improve the nutritional status in the Village Sukorejo Kindergarten students, for students who assessed their nutritional status is still lacking.Key Words: Nutritional Status, Childhood and Kindergarten, AnthropometryAbstrakStatus gizi adalah keadaan gizi seseorang, dalam hal ini dapat dideteksi dengan cara antropometri yaitu dengan mengukur ukuran tubuh, misalnya berat badan (BB), tinggi badan (TB), lingkaran lengan atas (LLA). Kegiatan ini biasa dilakukan oleh semua orang tetapi harus dilatih terlebih dahulu. Tim IKIP PGRI ingin menindaklanjuti program pembinaan pengajar TK dalam memahami status gizi anak balita dengan memberikan pelatihan pengukuran gizi, pembuatan alat pengukur gizi, simulasi, dan tanya jawab. Sasaran kegiatan ini meliputi guru-guru TK se-Kelurahan Sukorejo, Kecamatan Gunungpati, Kota Semarang, meliputi: TK Pertiwi 44, TK An-Nur, dan TK ABA 38 dengan permasalahan yang kini tengah dihadapi oleh di antaranya adalah: 1) kurangnya pengetahuan dalam mengidentifikasi status gizi anak balita secara visual; 2) kurang tersedianya alat pengukur status gizi; 3) kurangnya keterampilan membuat alat pengukur status gizi; 4) belum optimalnya penggunaan alat pengukur gizi anak balita. Hasil yang telah dicapai dari kegiatan pembinaan ini pengajar TK di kelurahan Sukorejo mampu memahami status gizi anak balita dengan baik dan mampu membuat alat ukur status gizi, serta mampu mengaplikasikan alat ukur status gizi (antropometri) dengan benar. Selain itu, tim pengabdian juga memberikan bantuan stimulus untuk meningkatkan status gizi siswa TK di Kelurahan Sukorejo, untuk siswa yang dinilai masih kurang status gizinya.Kata Kunci: Status Gizi, Anak Balita dan TK, Antropometri